2016
DOI: 10.1111/boj.12452
|View full text |Cite
|
Sign up to set email alerts
|

Diverse evolutionary pathways shaped 5S rDNA of species of tribe Anemoneae (Ranunculaceae) and reveal phylogenetic signal

Abstract: Anemone sensu lato (including Pulsatilla and Hepatica), tribe Anemoneae (Ranunculaceae), is arranged into two subgenera, Anemone and Anemonidium, with basic chromosome numbers x = 8 and x = 7, respectively. We elucidated the level of divergence of 5S rDNA unit arrays between the subgenera, determined intra‐individual and interspecific sequence variation and tested 5S rDNA phylogenetic signal in revealing the origin of polyploid species. High intra‐individual nucleotide diversity and the presence of 5S rDNA uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
2
8
0
1
Order By: Relevance
“…Observed intraspecific, interspecific and intra‐individual polymorphism of the intergenic spacer of the 5S cistron in Quercus (in terms of unit length, GC content and nucleotide sequence) is consistent with many other plant groups (Forest et al., 2005; Fulnecěk et al., 2002; Grimm & Denk, 2010; Mahelka et al., 2013; Mlinarec et al., 2016; Negi et al., 2002; Tynkevich & Volkov, 2019). The intra‐individual and/or intraspecific occurrence of two (or more) distinct 5S array types (e.g., “short” and “long” units in members of sect.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Observed intraspecific, interspecific and intra‐individual polymorphism of the intergenic spacer of the 5S cistron in Quercus (in terms of unit length, GC content and nucleotide sequence) is consistent with many other plant groups (Forest et al., 2005; Fulnecěk et al., 2002; Grimm & Denk, 2010; Mahelka et al., 2013; Mlinarec et al., 2016; Negi et al., 2002; Tynkevich & Volkov, 2019). The intra‐individual and/or intraspecific occurrence of two (or more) distinct 5S array types (e.g., “short” and “long” units in members of sect.…”
Section: Discussionsupporting
confidence: 74%
“…The 5S rRNA genes form gene arrays analogous to the 35S rDNA, localized on one or a few chromosomes, usually far from the nucleolus organizer regions (NORs) of the 35S rDNA (http://www.plantrdnadatabase.com/; see Ribeiro et al., 2011 for selected oak and beech species). In higher plants, the number of repeats per genome ranges from hundreds to thousands (Cloix et al., 2000), and the 5S rRNA coding regions are separated by a generally variable, nontranscribed intergenic spacer (5S‐IGS) with high phylogenetic resolution (e.g., Blattner, 2009; Forest et al., 2005; Garcia & Kovařik, 2013; Grimm & Denk, 2010; Mlinarec et al., 2016). Its interindividual and intragenomic variability is probably the main reason why it is little used.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that the IGS of Arabidopsis thaliana contains short-sequence motifs involved in initiation (external elements of the promoter) and termination (terminator) of 5S rDNA transcription ( Douet and Tourmente, 2007 ; de Souza et al, 2020 ). Thus, one would expect that these regions are to be relatively conservative, as has been demonstrated in several taxonomic groups ( Falistocco et al, 2007 ; Tynkevich and Volkov, 2014 ; Tynkevich et al, 2015 ; Mlinarec et al, 2016 ; Ishchenko et al, 2018 ; Alexandrov et al, 2021 ). However, the existing knowledge of the organization of external promoter elements and their molecular evolution is still incomplete.…”
Section: Introductionmentioning
confidence: 86%
“…Additive inheritance of both parent variants of 5S and 35S rDNA is usually observed in the first generation of interspecific hybrids/allopolyploids. However, in ancient allopolyploids, 35S rDNA can be the subject of interlocus sequence conversion ( Volkov et al, 1999a , b , 2007 ; Vizoso et al, 2011 ), while different variants of 5S rDNA can coexist in a plant genome for a long time without being homogenized ( Fulnecek et al, 2002 ; Song et al, 2012 ; Mahelka et al, 2013 ; Mlinarec et al, 2016 ; Volkov et al, 2017 ; Ishchenko et al, 2018 ). Especially, a significant sequence divergence was found for spatially distant 5S rDNA variants that are located in different loci of the same chromosome set ( Cronn et al, 1996 ; Vozárová et al, 2021 ) and for different parent loci in genomes of hybrid origin ( Fulnecek et al, 2002 ; Matyasek et al, 2002 ), while repeats from the same locus appeared to be highly homogenized.…”
Section: Introductionmentioning
confidence: 99%
“…Кодувальна ділянка є еволюційно консервативною, і помітна різниця в її послідовності спостерігається лише за порівняння віддалених таксонів. Натомість, послідовність МГС швидко накопичує мутації і нерідко значно відрізняється вже на міжвидовому або міжпопуляційному рівні [7,[14][15][16][17][18][19].…”
unclassified